2000
DOI: 10.1093/emboj/19.11.2652
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of 14-3-3 proteins in nuclear localization of telomerase

Abstract: Maintenance of telomeres is implicated in chromosome stabilization and cell immortalization. Telomerase, which catalyzes de novo synthesis of telomeres, is activated in germ cells and most cancers. Telomerase activity is regulated by gene expression for its catalytic subunit, TERT, whereas several lines of evidence have suggested a post‐translational regulation of telomerase activity. Here we identify the 14‐3‐3 signaling proteins as human TERT (hTERT)‐binding partners. A dominant‐negative 14‐3‐3 redistributed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
232
1
4

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 276 publications
(246 citation statements)
references
References 61 publications
9
232
1
4
Order By: Relevance
“…Regulation of subcellular localization of the binding partner is one of the main 'modes of function' of the 14-3-3 proteins (Muslin and Xing, 2000;Tzivion et al, 2001). Examples of this mode of regulation include protein phosphatase Cdc25C (Dalal et al, 1999), histone deacetylase (Grozinger and Schreiber, 2000), telomerase (Seimiya et al, 2000) and protein kinase U-a (Zhang et al, 1999). In agreement with this hypothesis, the 14-3-3 protein has been shown to physically interact with both parts of bipartite NLS of phosphorylated FOXO4 (fragment 11-213) (Obsilova et al, 2005).…”
Section: Phosphorylation Of the Foxo Dbdmentioning
confidence: 99%
“…Regulation of subcellular localization of the binding partner is one of the main 'modes of function' of the 14-3-3 proteins (Muslin and Xing, 2000;Tzivion et al, 2001). Examples of this mode of regulation include protein phosphatase Cdc25C (Dalal et al, 1999), histone deacetylase (Grozinger and Schreiber, 2000), telomerase (Seimiya et al, 2000) and protein kinase U-a (Zhang et al, 1999). In agreement with this hypothesis, the 14-3-3 protein has been shown to physically interact with both parts of bipartite NLS of phosphorylated FOXO4 (fragment 11-213) (Obsilova et al, 2005).…”
Section: Phosphorylation Of the Foxo Dbdmentioning
confidence: 99%
“…The hTERT-HA expression vector has been described (Seimiya et al 2000). The HAubiquitin expression vector was constructed by cloning the BamHI and XbaI fragment encoding the ubiqutin cDNA into pcDNA3.1 (Invitrogen) (J.S.…”
Section: Expression Vectorsmentioning
confidence: 99%
“…One possible mechanism for the post-translational modifications of telomerase is the interaction of hTERT with accessory proteins. Recently, it was reported that 14-3-3 proteins, which have been proposed to be important in controlling intracellular signaling cascades by associating with a number of different signaling proteins (Moorhead et al, 1996) and to work as molecular chaperones or to regulate intracellular localization of their binding partners (Yang et al, 1999), are post-translational modifiers of telomerase that function by controlling the intracellular localization of hTERT (Seimiya et al, 2000).…”
Section: Introductionmentioning
confidence: 99%